Alternate synthesis of appetite suppressant (R)-2-benzylmorpholine employing Sharpless asymmetric epoxidation strategy - Viswanadh, N.; Mujumdar, P.; Sasikumar, M.; Kunte, S. S.; Muthukrishnan, Murugan (Tetrahedron Letters, 2016)
An alternate synthesis of (R)-2-benzylmorpholine 1, an appetite suppressant agent has been accomplished starting from readily available trans-cinnamyl alcohol employing Sharpless asymmetric epoxidation strategy as a key step, with an overall yield of 24%. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: (R)-2-Benzylmorpholine; Appetite suppressant; Sharpless asymmetric epoxidation